Melampaui Pendekatan Legalistik: Hukum Adat Marind Sebagai Basis Keadilan Restoratif Dalam Penanganan Anak Berhadapan Dengan Hukum (Studi Di Kabupaten Merauke, Papua Selatan) - Silubun, Anton Johanis; Saragih, Dapot Pardamean (Universitas Musamus, 2025)
The handling of Children in Conflict with the Law (CICL) within Indonesia’s juvenile justice system continues to face significant challenges, particularly the dominance of a legalistic and procedural approach that insufficiently addresses the social and cultural dimensions of children’s lives. This issue becomes more complex in indigenous communities where customary legal systems function as living norms for conflict resolution. This study aims to examine the role of Marind customary law in handling CICL cases in Merauke Regency, assess its compatibility with restorative justice principles, and formulate an integrative model that harmonizes customary law and state law. Employing an empirical juridical approach, data were collected through semi-structured interviews, participatory observation, and document analysis. The findings reveal that CICL handling remains largely formalistic, limiting the involvement of indigenous institutions and weakening children’s social reintegration. Conversely, Marind customary law demonstrates conflict resolution mechanisms aligned with restorative justice principles, emphasizing deliberation, social responsibility, and relational restoration. This study proposes a hybrid model of CICL handling that positions customary institutions as primary mediators, supported by law enforcement authorities to ensure the protection of children’s rights. This model contributes to the operationalization of legal pluralism and offers a practical policy alternative for reforming the juvenile justice system in South Papua.